Year-round dynamics of amplicon sequence variant communities differ among eukaryotes, Imitervirales and prokaryotes in a coastal ecosystem. Issue 12 (28th December 2021) - Prodinger, Florian; Endo, Hisashi; Takano, Yoshihito; Li, Yanze; Tominaga, Kento; Isozaki, Tatsuhiro; Blanc-Mathieu, Romain; Gotoh, Yasuhiro; Hayashi, Tetsuya; Taniguchi, Etsunori; Nagasaki, Keizo; Yoshida, Takashi; et al.
ABSTRACT: Coastal microbial communities are affected by seasonal environmental change, biotic interactions and fluctuating nutrient availability. We investigated the seasonal dynamics of communities of eukaryotes, a major group of double-stranded DNA viruses that infect eukaryotes (order Imitervirales ; phylum Nucleocytoviricota ), and prokaryotes in the Uranouchi Inlet, Kochi, Japan. We performed metabarcoding using ribosomal RNA genes and viral polB genes as markers in 43 seawater samples collected over 20 months. Eukaryotes, prokaryotes and Imitervirales communities characterized by the compositions of amplicon sequence variants (ASVs) showed synchronic seasonal cycles. However, the community dynamics showed intriguing differences in several aspects, such as the recovery rate after a year. We also showed that the differences in community dynamics were at least partially explained by differences in recurrence/persistence levels of individual ASVs among eukaryotes, prokaryotes and Imitervirales . Prokaryotic ASVs were the most persistent, followed by eukaryotic ASVs and Imitervirales ASVs, which were the least persistent. We argue that the differences in the specificity of interactions (virus–eukaryote vs prokaryote–eukaryote) as well as the niche breadth of community members were at the origin of the distinct community dynamics among eukaryotes, their viruses and prokaryotes. Abstract : A 1-year observation of coastal microbial communities revealed similar but different community dynamics for eukaryotes, their viruses and prokaryotes.